Side-stream sludge treatment using free nitrous acid selectively eliminates nitrite oxidizing bacteria and achieves the nitrite pathway - Wang, Qilin; Ye, Liu; Jiang, Guangming; Hu, Shihu; Yuan, Zhiguo (Water research (Oxford), 2014)
Nitrogen removal via nitrite (i.e. the nitrite pathway) is beneﬁcial for carbon-limited biological wastewater treatment plants. This study presents a novel strategy for achieving the nitrite pathway, which involves recirculating a portion of the activated sludge through a side-stream sludge treatment unit, where the sludge is subject to treatment with free nitrous acid (FNA i.e. HNO2). The strategy is proposed based on a novel discovery reported in this work that in the concentration range of 0.24–1.35 mg HNO2−–N/L, FNA is substantially more biocidal to nitrite oxidizing bacteria (NOB) than to ammonium oxidizing bacteria (AOB). Two sequencing batch reactors (SBR) treating synthetic domestic wastewater were used to demonstrate the concept, with one serving as an experimental reactor and the other as a control. In the experimental system, 22% of the sludge from the SBR was transferred to the side-stream treatment unit each day, and was subject to FNA treatment at 1.35 mg N/L for 24 h and then returned to the SBR. The nitrite pathway was rapidly (in 15 d) established in the experimental reactor with an average nitrite accumulation ratio (NO2−–N/(NO2−–N + NO3−–N) × 100%) of above 80%. Fluorescence in-situ hybridization demonstrated that the NOB population in the experimental reactor was 80% lower than that in the control reactor, indicating that the majority of NOB were eliminated from the experimental reactor. The FNA-based strategy for establishing the nitrite pathway substantially improved total nitrogen removal, and did not increase N2O emission or deteriorate sludge settleability. The strategy can be easily integrated with a previously demonstrated strategy, which enhances methane production through pre-treatment of secondary activated sludge, to enable maximum energy recovery while achieving improved nitrogen removal. [Display omitted] •FNA inactivates NOB to a much larger extent than it does on AOB.•Sludge treatment using FNA is effective in establishing the nitrite pathway.•Sludge treatment using FNA does not increase N2O emission or SVI.•FNA-based method could potentially improve nitrogen removal and methane production simultaneously.